Modulation of immune genes in the mucosal-associated lymphoid tissues of cobia by Sarcodia suae extract - Vakaloloma, Ulamila; Ho, Thi Hang; Loh, Jiun-Yan; Chong, Chou Min; Wangkahart, Eakapol; Lee, Meng-Chou; Nan, Fan-Hua; Lai, Hung-Chih; Lee, Po-Tsang (Springer Science, 2023)
Rachycentron canadum (cobia) is a marine fish species of high economic value in aquaculture due to its fast growth rate and good feed conversion efficacy. Regrettably, the industry has been affected by significant setbacks from high mortality due to diseases. Consequently, an improved perception of innate immunity correlated to each mucosal-associated lymphoid tissue (MALT) in teleost fish is necessary to understand hosts’ response towards infections better. The utilization of polysaccharides in seaweed to stimulate the immune system has gathered unprecedented attention. The present study examined the immunostimulatory effects of Sarcodia suae water extracts (SSWE) on in vivo gill-, gut- and skin-associated lymphoid tissues (GIALT, GALT, and SALT) via immersion and oral ingestions. The GIALT genes (TNF-α, Cox2, IL-1β, IL-6, IL-8, IL-17 A/F1-3, IL-11, IL-12, IL-15, IL-18, MHCIa, IgM, and IgT) except IL-10 recorded positive upregulations in a dose-dependent manner post 24 h immersion in SSWE, indicating the algae extract contained bioactive compounds that could stimulate the immune genes. The upregulation of IL-12, IL-15, and IL-18 in the gills and hindgut post-SSWE immersion indicated that the extract could promote Th1-related responses in the MALTs. The modulation of immune gene expressions in the feeding trial was less potent than in the SSWE immersion. These findings indicated that the SSWE stimulated robust immune responses in both the GIALT and GALT of cobia. This suggests that the SSWE could be further explored as an effective immersive stimulant for fish, enhancing their immune system against pathogens